A genetic polymorphism for translocator protein 18 kDa affects both in vitro and in vivo radioligand binding in human brain to this putative biomarker of neuroinflammation - Kreisl, William C (Nature Publishing Group, 2013)
Second-generation radioligands for translocator protein (TSPO), an inflammation marker, are confounded by the codominant rs6971 polymorphism that affects binding affinity. The resulting three groups are homozygous for high-affinity state (HH), homozygous for low-affinity state (LL), or heterozygous (HL). We tested if in vitro binding to leukocytes distinguished TSPO genotypes and if genotype could affect clinical studies using the TSPO radioligand [(11)C]PBR28. In vitro binding to leukocytes and [(11)C]PBR28 brain imaging were performed in 27 human subjects with known TSPO genotype. Specific [(3)H]PBR28 binding was measured in prefrontal cortex of 45 schizophrenia patients and 47 controls. Leukocyte binding to PBR28 predicted genotype in all subjects. Brain uptake was ∼40% higher in HH than HL subjects. Specific [(3)H]PBR28 binding in LL controls was negligible, while HH controls had ∼80% higher binding than HL controls. After excluding LL subjects, specific binding was 16% greater in schizophrenia patients than controls. This difference was insignificant by itself (P=0.085), but was significant after correcting for TSPO genotype (P=0.011). Our results show that TSPO genotype influences PBR28 binding in vitro and in vivo. Correcting for this genotype increased statistical power in our postmortem study and is recommended for in vivo positron emission tomography studies.